"Ebinyo"-The Practice of Infant Oral Mutilation in Uganda - Margaret N. Wandera; Margaret N. Wandera; Betsy Kasumba (Frontiers Media S.A., 2017)
Infant oral mutilation (IOM) is a traditional method of extracting un-erupted teeth practiced in several Sub-Saharan African countries including Uganda. This practice is referred to as "ebinyo" by Bantu-speaking Ethnic groups, though it has several terms depending on cultural group and researcher. The un-erupted tooth is gouged out as a cure for medical symptoms in infants that include high fevers and diarrhea. The spreading of IOM practice in African populations is blamed on poor health literacy with regard to the common childhood illnesses. One study in Uganda revealed that adverse cases following IOM seen in the hospital peaked in tandem with the malaria and diarrheal disease cases. This paper is a review of the practice with a particular focus on Uganda as presented in literature compiled from PubMed, Dentaid, Google Scholar, Local Uganda sources, and the authors' observations. The paper explains reason for the persistence of the practice, and to further inform on IOM to health practitioners who were previously unaware of the practice.